Pengaruh Akuntabilitas, Transparansi, dan Partisipasi Masyarakat Terhadap Pengelolaan APBDesa - Merisa Oktaria; Rinto Alexandro (Edunomics Journal, 2021)
The village is a social institution that has a very important position and has very close direct interactions with the community. The village is an autonomous institution with its own traditions, customs and laws that are deeply rooted and relatively independent from interference from powers outside the institution. This research has its own reasons for choosing the APBDesa program for this interest because the APBDesa has major implications for the development of a region. The method used in this research is quantitative method. The type of data used in this research is quantitative data, namely, data in the form of numbers and questionnaire assistance to obtain answers to the research objectives. The population in this study was the village government of Tewang Karangan totaling 36 people and the population based on the KK of 489 people. The sample is part of the number and characteristics possessed by the population with the sampling technique using purposive sampling. The analytical tool used is multiple linear analysis using the SPSS 25 program